2020
DOI: 10.1080/14683849.2020.1724511
|View full text |Cite
|
Sign up to set email alerts
|

Turkish leaders and their foreign policy decision-making style: a comparative and multi-method perspective

Abstract: Using both quantitative and qualitative research techniques, we investigate the effect of leaders' style and personality on foreign policy. The study examines six Turkish leaders, Süleyman Demirel, Bülent Ecevit, Necmettin Erbakan, Recep Tayyip Erdoğan, Abdullah Gül, and Turgut Özal, and 18 foreign policy cases to answer the followings: Do Turkish leaders differ from each other in terms of their personality traits and styles? How did their styles affect their foreign policy choices? How did they react to vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…This interpretation of his trait combinations in the complex context of Iranian political scene reveals a certain degree of compatibility with his role in the achievement of the deal. Like Çuhadar et al (2020), we suggest that LTA‐based research should be complemented with in‐depth case analysis for a better conceptualization of the impact of leaders’ styles on foreign policy.…”
Section: Rouhani’s Leadership Stylementioning
confidence: 73%
“…This interpretation of his trait combinations in the complex context of Iranian political scene reveals a certain degree of compatibility with his role in the achievement of the deal. Like Çuhadar et al (2020), we suggest that LTA‐based research should be complemented with in‐depth case analysis for a better conceptualization of the impact of leaders’ styles on foreign policy.…”
Section: Rouhani’s Leadership Stylementioning
confidence: 73%
“…Many scholars have successfully applied LTA in a variety of political contexts (e.g. Cuhadar et al 2021 ; Dyson 2006 ; Hermann 1987 ; Kesgin 2019 , 2020 ; Kille and Scully 2003 ). According to LTA, political personality is a combination of seven traits: belief in the ability to control events, conceptual complexity, the need for power, distrust of others, in-group bias; self-confidence, and task orientation.…”
Section: Role Theory and Leadership Trait Analysismentioning
confidence: 99%
“…3 In fact, leadership styles have been broadly documented as a source of influence, direction, and redirection in foreign policy (e.g. Cuhadar et al 2017b , 2021 ; Dyson 2006 ; Hermann 2003 ; Kesgin 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dueling Personalities and Leadership Styles: Gül, Erdoğan, and the Parliament in Turkey's… prime minister. Gül as a politician "respected constraints and used his skills and status to persuade rather than to force others to follow his ideas or policy choices", as Cuhadar et al (2021) observed. 22 Gül's choice to let the parliament freely (without party discipline) 23 decide on the matter showed his preference to work towards his goals within the parameters of the Turkish constitution, which designated the parliament as the ultimate decision-unit for such occasions.…”
mentioning
confidence: 96%
“…This table also corrects a typo in Erdoğan's self-confidence score printed as .36 inCuhadar et al (2017b).c The world and Middle East means and standard deviations (in parentheses) obtained from Margaret Hermann (email communication). d The Turkish leaders comparison group is fromCuhadar et al (2021), which looks at multiple Turkish leaders. These scores are included for readers' comparison only.…”
mentioning
confidence: 99%